Aspects of the reproductive biology and aquaculture potential of mangrove red snapper (Lutjanus argentimaculatus) - Ostrowski, B.F. (Universiti Putra Malaysia, 2015)
Mangrove red snapper broodstock (mean weight 4.4 kg) were stocked in flow-through seawater tanks and spawned spontaneously after 11 days. Spawning continued during a period of six weeks from late August to mid-October producing 207,000 - 1,870,000 eggs per spawning event. Fertilisation rate of the eggs was in the range 64-99% with a mean hatching rate of 81%. Survival to first feeding was in the range 18-99% (mean 75%). Subsequent larval mortality was high with 58% maximum survival to day 10 and less than 1% by day 20. Mouth gape of developing larvae was 99 mu m at first opening whilst the mean lorica width of cultured rotifers was 138 mu m. Smaller size initial feeds such as oyster eggs (50 mu m) or commercial micro-particulate feeds (25-60 mu m) are recommended for improved survival of first feeding larvae. Data collected in 1991 and 1992, when spawning was observed from April - May and August - October respectively, indicate that mangrove red snapper on the west coast of Sabah have two spawning peaks during the year.